2022
DOI: 10.1007/s10068-022-01171-3
|View full text |Cite
|
Sign up to set email alerts
|

Garden cress gum and maltodextrin as microencapsulation coats for entrapment of garden cress phenolic-rich extract: improved thermal stability, storage stability, antioxidant and antibacterial activities

Abstract: The obtained garden cress 6-day sprouts phenolic-rich extract (GCSP) contained efficient health-promoting antioxidant-phenolic compounds. To improve the stability, bioavailability, and functional properties of these valuable phenolic compounds, GCSP was encapsulated by freeze-drying technique using different ratios of garden cress gum (GG) and maltodextrin (M) in the absence and presence of sonication (S). The prepared S/GG-microcapsule retained the highest phenolic content (95%), antioxidant activity (141.6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
2
5
1
Order By: Relevance
“…for ABTS and DPPH, respectively). This agrees with the results reported by Sarabandi et al [53], in which an encapsulated eggplant peel extract produced with MD had higher antioxidant capacity than that with AG, while Abdel-Aty et al [54] found that the use of gum and maltodextrin as microencapsulation coats favored the retention of antioxidant compounds such as the phenolic content of garden cress. Furthermore, the selection of coating material has a considerable impact on the properties of the encapsulates including solubility, stability, and quality.…”
Section: Antioxidant Activitysupporting
confidence: 91%
See 1 more Smart Citation
“…for ABTS and DPPH, respectively). This agrees with the results reported by Sarabandi et al [53], in which an encapsulated eggplant peel extract produced with MD had higher antioxidant capacity than that with AG, while Abdel-Aty et al [54] found that the use of gum and maltodextrin as microencapsulation coats favored the retention of antioxidant compounds such as the phenolic content of garden cress. Furthermore, the selection of coating material has a considerable impact on the properties of the encapsulates including solubility, stability, and quality.…”
Section: Antioxidant Activitysupporting
confidence: 91%
“…for ABTS and DPPH, respectively). This agrees with the results reported by Sarabandi et al [53], in which an encapsulated eggplant peel extract produced with MD had higher antioxidant capacity than that with AG, while Abdel-Aty et al [54] found that the use of gum and maltodextrin as microencapsulation coats favored the retention of antioxidant The infusion of plants is a relevant extraction method that eliminates the use of organic solvents. In addition, by obtaining nontoxic extracts with antioxidant capacity through this method, the isolation and purification of the antioxidant compounds is unnecessary [49].…”
Section: Antioxidant Activitysupporting
confidence: 91%
“…While the initial thermal degradation of the ACG-HRP occurred between 145 and 275 °C and caused a lesser mass loss of 2–9%. The initial mass loss is caused by removing the water/moisture entrapped in the molecular structure 35 . Additionally, the second mass decomposition was found around 240–335 °C for ACG-complex and 275–375 °C for ACG-HRP, and they retained 71 and 80% of their weights, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…#Approximate position of Figure 1# PDI demonstrates the degree for homogeneity and uniformity in distribution of particle size [22]. The PDI values for nanocapsulation of OEO and BEO were 0.376 ± 0.051 and 0.346 ± 0.028 as well as no signi cant difference was observed between these substances.…”
Section: #Approximate Position Of Table 2#mentioning
confidence: 98%